Studies on micro and macro mineral profiles of seminal plasma of Tarai buffalo bulls - SINGH, BEERENDRA; GUPTA, H P; SINGH, HARPAL (The Indian Journal of Animal Reproduction, 2007)
A total of 60 semen ejaculates were collected from six Tarai buffalo bulls using sterilized artificial vagina twice weekly and were evaluated as per standard procedures for the routine tests. Seminal plasma was separated by centrifugation. The various macro and micro mineral constituentsof the seminal plasma were analyzed. Mmanganese, iron, copper, cobalt and zinc averaged 0.029±0.002,2.85±0.16, 0.031±0.002, 0.177±0.019 and 2.54±0.05 mg/di, respectively. The macro minerals, viz.sodium, potassium, calcium and phosphorus averaged 272.85±9.84, 75.78±3 .23, 42.01±0.0land7.55±0.16 mg/di, respectively. On the basis of present investigation, it may be concluded that microand macro mineral constituents in Tarai buffalo bulls were in the normal rang.
Keywords: Tarai buffalo; Seminal Plasma; Macro and Micro Mineral.